Dual-structure-breaking electrolyte enables practical cadmium-metal battery - Yang-Feng Cui; Hao-Bin Song; Jing-Jing Yao; Qi Hao; Xue-Liang Li; Yi-Fan Li; Bin-Bin Guo; Yun-Hai Zhu; Hui Ying Yang (Nature Communications)
Abstract High-energy aqueous metal batteries are promising candidates for the next-generation energy storage systems but face critical challenges of dendrite and corrosion in metal negative electrodes. To address these issues, we report an aqueous cadmium-metal battery employing a fast-kinetics structure-breaking electrolyte composed of CdCl2 and NH4Cl. The addition of NH4Cl induces the formation of dual structure breakers, NH4 + and tetrachlorocomplex ([CdCl4]2–), which facilitate fast charge transfer kinetics in aqueous cadmium-metal batteries and endow dendrite-free/corrosion-resistant capabilities to Cd negative electrodes. This tailored electrolyte realizes a convincing Coulombic efficiency (99.93%) for Cd plating/stripping behavior at a high Cd utilization of 55%, making it suitable for practical applications. Moreover, the fast-kinetics aqueous cadmium-metal batteries exhibit remarkable compatibility with diverse types of positive electrodes, including conversion-, coordination-, intercalation- and capacitance-type, offering enhanced rate performance and durable rechargeable stability. These results establish a robust and scalable aqueous battery design for sustainable energy storage systems.